Linear Diophantine Fuzzy Set Theory Applied to BCK/BCI-Algebras - Ghulam Muhiuddin; Madeline Al-Tahan; Ahsan Mahboob; Sarka Hoskova-Mayerova; Saba Al-Kaseasbeh (Mathematics, 2022)
In this paper, we apply the concept of linear Diophantine fuzzy sets in <semantics>BCK/BCI</semantics>-algebras. In this respect, the notions of linear Diophantine fuzzy subalgebras and linear Diophantine fuzzy (commutative) ideals are introduced and some vital properties are discussed. Additionally, characterizations of linear Diophantine fuzzy subalgebras and linear Diophantine fuzzy (commutative) ideals are considered. Moreover, the associated results for linear Diophantine fuzzy subalgebras, linear Diophantine fuzzy ideals and linear Diophantine fuzzy commutative ideals are obtained.